Ultrasound appearances after mesh implantation--evidence of mesh contraction or folding? - Svabík, Kamil; Martan, Alois; Masata, Jaromir; El-Haddad, Rachid; Hubka, Petr; Pavlikova, Marketa (International urogynecology journal, 2011)
INTRODUCTION AND HYPOTHESIS: Polypropylene meshes are frequently used in abdominal and vaginal reconstructive surgery. Recently, several authors have claimed that mesh-associated complications may be linked to mesh shrinkage. We have performed a prospective study with postoperative follow-up by ultrasound examination at two time points after Prolift anterior implantation to assess changes in the ultrasound appearance of mesh implants over time. METHODS: We assessed 36 patients who had undergone mesh implantation with Prolift anterior mesh for the correction of symptomatic anterior vaginal wall prolapse. During the surgery, we measured the actual midline length of the mesh (initial length). On the fourth postoperative day, we performed a vaginal ultrasound examination (US) to measure mesh length in the midsagittal plane. A second US was performed 3-5 months after surgery to repeat this measurement. RESULTS: There was a significant difference in mesh length determined before and 4 days after surgery (90.3 vs. 57.1 mm, P = <0.0001) indicating intraoperative folding. On comparing early and late postoperative ultrasound measurements, there was a reduction in length from 57.1 to 48.3 mm (P < 0.0001), indicating possible shrinkage or retraction. CONCLUSIONS: Intraoperative folding seems to be responsible for a large part of the difference between preoperative (in vitro) and postoperative (US) measurements of mesh dimensions, suggesting that surgical techniques may require adjustment.
Keywords: Ultrasonography; prolaps pánevních orgánů; Postoperative Complications; Surgical Mesh; gynekologické chirurgické výkony; chirurgické síťky; následné studie; Gynecologic Surgical Procedures; Prospective Studies; pooperační komplikace; Pelvic Organ Prolapse; Follow-Up Studies; lidé; selhání zařízení; ženské pohlaví; Humans; Equipment Failure; Female; Vagina; vagina; lidé středního věku; ultrasonografie; Middle Aged; prospektivní studie